The many shades of open banking: A comparative analysis of rationales and models - Giuseppe Colangelo; Pankhudi Khandelwal (Internet Policy Review, 2025)
Despite its growing success, open banking (OB) struggles to present a coherent identity. Indeed, despite its widespread adoption around the world, various models can be identified based on rationales, the nature of data-sharing obligations, and the standardisation process. Against this background, the paper aims to evaluate the consistency of OB policies. To this end, our analysis adopts a novel approach by examining the primary rationales behind OB regulatory initiatives in some major countries (i.e., the EU, UK, Australia, the US, India, and Singapore). Identifying these rationales is crucial for assessing whether the specific features of OB solutions implemented in each country are aligned with the intended policy goals. Therefore, the paper first identifies the primary rationales supporting OB initiatives in these countries and then examines their datasharing and standardisation approaches. By mapping the primary rationales and models in terms of data-sharing obligations and standardisation solutions, the comparative analysis shows that variations in models and approaches among the examined jurisdictions do not necessarily reflect differences in the policy goals pursued through the OB regime. As a result, by recommending regulatory and technical solutions that better align with the intended policy goals of an OB regime, such a comparative analysis can assist policymakers in countries considering the introduction of open banking to design a model that best suits their needs.
Keywords: 300; Open banking; FinTech; Standards; Data; Regulation